Military intelligence and early modern warfare: the Dutch East India Company and China 1622-1624 - Noordam, Barend (The dynamics of transculturality, 2015)
The VOC’s military campaign to gain access to the Chinese market reveals a great deal of reliance on (military) intelligence as a means to reach decisions on the type of military action that was to be taken. A comparison with contemporaneous intra-European wartime practices reveals that the VOC, in this transcultural context of warfare, resorted to many of the same means of intelligence gathering and implementation, revealing an institutional flow between European and Chinese theatres of action. The essential difference, however, was the need to rely on intercultural mediators who could act as agents in the information flow in order to gain the intelligence and assistance the VOC needed. The Chinese Ming Empire was nevertheless able to exert control over intercultural mediators who aided the company. The Ming Empire thus displayed enough political cohesion in the face of European military strength to force the Dutch to conform to its demands. In the end, the Dutch campaign failed because of a lack of grand strategic intelligence, which could only be supplied by the kind of high-level intercultural mediators that the Dutch could not access, and because of the Batavia leadership’s flawed assumption that military pressure was enough to force compliance from the Ming Empire. This flawed assumption stemmed from an erroneous reading of Portuguese successes in gaining access to the Chinese markets and reveals a lack of understanding of the internal political workings of the Chinese bureaucracy, its relationship with Beijing, and its entanglements with powerful local merchants.
First Online: 10 October 2014
Gesehen am 02.06.2020